2015
DOI: 10.1093/asj/sjv075
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Differentiation Potential of Human Mesenchymal Stem Cells From Adipose Tissue Harvested by Water Jet-Assisted Liposuction

Abstract: 3 Therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 49 publications
0
34
0
1
Order By: Relevance
“…Unlike the immunocompromised nude mice receiving purified ASC cultures,(43) immunocompetent human patients typically receive fat grafts containing a variable, but low (2 to 8%) fraction of ASCs. (44, 45)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the immunocompromised nude mice receiving purified ASC cultures,(43) immunocompetent human patients typically receive fat grafts containing a variable, but low (2 to 8%) fraction of ASCs. (44, 45)…”
Section: Discussionmentioning
confidence: 99%
“…Still, various methods of fat harvest and processing may affect adipocyte viability and stem cell fraction. (5962) While optimization of the ASC-rich stromal vascular fraction of lipoaspirate may favor improved graft retention,(45) it may also increase the risk of exposure of ASCs to occult, residual tumor stroma. (45) All patients were treated at high-volume cancer centers and likely had access to timely cancer treatment and appropriate administration of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…85,86 Preliminary in vitro and rodent studies with water-jet-assisted liposuction suggest that it improves ASC content, results in more viable adipocytes, and increases volume retention of grafts. 87,88 Harvest cannula size has also been investigated to reduce shear stress and improve graft viability. Larger, 5-to 6-mm harvesting cannulas seem to improve adipocyte viability in cell culture and in animal models.…”
Section: Emerging Strategiesmentioning
confidence: 99%
“…An elegant series of experiments recently demonstrates that lipoaspirates harvested with UAL and SAL share a similar proportion of viable adipose-derived stem cells with equivalent expression of regenerative genes and potential to differentiate into chondrocytes, adipocytes, or osteocytes [11]. Another technology, water jet-assisted liposuction (WAL) uses a dual-aperture cannula that simultaneously emits tumescence solution as a fan-shaped, pulsating jet through an anteriorly located aperture, and suction fluid and aspirated fat from a more posteriorly located side port [35, 46, 59]. Human fat harvested with WAL demonstrated greater viability using both colorimetric and glucose transport test assays, with greater retention by weight, less apoptosis by Annexin V expression, and increased revascularization by CD31 immunostaining when injected as a xenograft into a murine host [59].…”
Section: Discussionmentioning
confidence: 99%
“…Human fat harvested with WAL demonstrated greater viability using both colorimetric and glucose transport test assays, with greater retention by weight, less apoptosis by Annexin V expression, and increased revascularization by CD31 immunostaining when injected as a xenograft into a murine host [59]. Other work has suggested that fat harvested with WAL contains abundant CD34+ cells suggesting a stem cell-rich stromal vascular fraction although a control group was not utilized in this study [35]. Although human data are not available, rats engrafted with human adipose xenografts harvested with TLL demonstrate adipocyte viability, graft weight, and histology comparable to the Coleman technique [9].…”
Section: Discussionmentioning
confidence: 99%